Improving antimicrobial activity against endodontic biofilm after exposure to blue light-activated novel curcumin nanoparticle - Minhaco, Vivian Maria Tellaroli Rodrigues [UNESP]; Maquera Huacho, Patricia Milagros [UNESP]; Mancim Imbriani, Maria Júlia [UNESP]; Tonon, Caroline Coradi; Chorilli, Marlus [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP] (Elsevier, 2023)
New therapies involving natural products and nanobiotechnology open additional perspectives to reduce endodontic infections. Curcumin is a natural polyphenol extracted from the dry rhizome of curcuma long Linn with therapeutic properties for application in nanobiotechnology and as a photosensitizer for photodynamic therapy. This study aimed to synthesize a novel polymeric nanoparticle of poly (lactic-co-glycolic acid) (PLGA) loaded with curcumin (NP+Cur), and evaluate its antimicrobial activity against endodontic biofilms. Additionally, its biocompatibility using oral keratinocytes was assessed. The polymeric NP+Cur was prepared by the nanoprecipitation method. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were calculated for the three endodontic bacteria (Enterococcus faecalis, Streptococcus oralis and Actinomyces viscosus). Antibacterial activity of NP+Cur against single- and multispecies biofilm pre-formed on the botton 24-well plate and into dentin tubules of bovine teeth were evaluated by colony forming units and confocal laser scanning microscopy. The pre-irradiation time was 5 min followed by exposure to blue light-emitting diode at 450 nm for the photodynamic treatment. Cell viability using oral keratinocytes was assessed by Alamar Blue assay. MIC and MBC showed antibacterial activity of NP+Cur against endodontic bacteria. A treatment of pre-formed biofilms of endodontic bacteria with NP+Cur also significantly decreased bacterial viability. The concentration of 325 μg/mL of photoactivated NP+Cur was the one that most reduced the viability of the endodontic bacteria evaluated. Regarding biocompatibility, NP+Cur 325 μg/mL and pure nanoparticles showed a cell viability greater than 80%. The novel polymeric nanoparticles loaded with curcumin may be a promising adjunct use to treatment of endodontic infections.
Keywords: Biofilms; Curcumin; Photodynamic therapy; Polymeric nanoparticles